Expression and function of neuropeptide y receptors in human articular cartilage: influence of gender and osteoarthritis - Ferreira, Inês Sofia dos Santos Rodrigues (2018)
This work was funded by European Regional Development Fund (FEDER) through the Operational Programme Competitiveness Factors – COMPETE: HealthyAging 2020 (CENTRO-01–0145-FEDER-000012), and by National Funds through FCT-Foundation for Science and Technology under the Strategic Project UID/NEU/04539/2013 and the project PTDC/EMS-TEC/ 3263/2014